Development of STEM-PjBL-Based Teaching Materials to Enhance Students' Science Literacy on Acid-Base Topic - Amdayani, Susilawati; Dibyantini, Ratu Evina; Syafriani, Dewi; Dalimunthe, Makharany (Jurnal Pendidikan MIPA, 2025)
An essential skill for learning chemistry is science literacy, which includes attitudes toward science, the scientific method, application in practical settings, and conceptual comprehension. However, the previous research revealed that students’ science literacy among Indonesian undergraduate students is still low, especially when it comes to abstract and complicated concepts like acids and bases. The study aims to develop STEM-PjBl-based teaching materials on acid acid-base topic and evaluate their effectiveness in enhancing students' science literacy. The study employs the 4D development model. The product effectiveness test was conducted at the development stage using a quasi-experimental design in the form of a one-group pretest-posttest design. The research subjects were 90 chemistry education undergraduate students who took basic chemistry courses in the 2024/2025 academic year, consisting of 3 classes. Data was gathered by a science literacy test, validation sheets, and practicality surveys for lecturers. The validity of questionnaire responses was obtained by three experts' judgment using the kappa coefficient, the practicality questionnaire was also assessed using the kappa coefficient, while the validity of data on science literacy improvement was obtained through pre-test and post-test results. The results showed that the average kappa coefficient of expert validation of STEM-PjBL-based teaching materials is 0.88 (high validity). The practicality questionnaire produced an average kappa coefficient of 0.89 (high practicality). The effectiveness test obtained an average n-gain value of 0.65 (moderate), as evidenced by student involvement in designing projects to create soft drinks from natural ingredients through the PjBL model. The designing and evaluating scientific investigations indicator (n-gain 0.67) shows the most significant improvement because students were required to systematically design experimental procedures, including problem identification, variable determination, hypothesis formulation, planning tools, materials, and work steps following scientific principles.    Keywords: teaching materials, STEM-PjBL, science literacy, acid-base.